Adopsi Bank Digital Pada Kinerja Perbankan Di Bursa Efek Indonesia Tahun 2019-2021 (Universitas Gresik, 2023)
This study aims to obtain empirical evidence regarding the effect of digital bank adoption on banking performance on the Indonesia Stock Exchange. The independent variable used in this study is the adoption of ATM, Internet Banking and Mobile Banking, while the dependent variable is the measurement of Return on Assets (ROA), Operational Efficiency Ratio (REO), Net Operational Margin (NOM), Income Diversification (DP) and Projection Net Operating Income (PPBO). The population of this study are banking companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. Sampling was done by using purposive sampling method. The sample of this study consisted of 111 companies for three years of observation. This study uses multiple linear regression analysis to examine the effect of the independent variable on the dependent variable. The results showed that ATM did not have a significant effect on overall banking performance. Internet Banking has a significant influence on banking performance through operational efficiency. Mobile Banking has a significant influence on the company's performance through ROA and NOM and the three independent variables have not shown a significant effect, especially Banking Performance on DP and PPBO.